THE VALUE OF EVIDENCE-BASED PRACTICE TRAINING THROUGH TELEMEDICINE: DO WE NEED TO BE IN THE SAME ROOM?. (11th November 2018) - Longstreth, M; Slosser, A; Barry, R; Carrico, C; McKibbin, C
Abstract: Research has suggested that limited time, access, and understanding of evidence-based practices (EBPs) often limit rural practitioners from utilizing EBPs in everyday practice (Lee, 2016; Solomons & Spross, 2011). Telemedicine-based methods have been identified as a solution for implementing EBPs into rural and remote regions, where access to quality content may be limited (Parson, Merlin, Taylor, Wilkinson, & Hiller, 2003). However, little is known about training providers to deliver evidence-based psychosocial interventions by way of telemedicine. To better understand the benefits and barriers to using telemedicine to deliver EBP training, individuals who completed an online telemedicine course designed to certify them to deliver an evidence-based caregiver program were contacted. All participants had taken part in eight two-hour online training sessions. Audio recordings were created from these calls, transcribed, and coded for common themes. Participants were seven female adults with an average age of 58.43 years (SD = 13.41). All participants were employed in a rural setting, and the majority endorsed working in social work or medical professions. Two primary themes emerged as barriers to using a telemedicine platform to teach EBPs: (1) individual learning differences and (2) technology problems. Further, three themes emerged as benefits to using a telemedicine platform: (1) peer support, (2) facilitator competence, and (3) convenience. When considering the utilization of online telemedicine platforms to communicate EBPs, one must consider overcoming key barriers to effective training, such as establishing and maintaining rapport with and highlighting personal connections to trainees to maintain participant engagement.